Mu’nah Dalam Operasional Pegadaian Syariah - Inatul Hinaya; Muslimin Kara; Sirajuddin Sirajuddin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Since 2018 the central sharia pawnshop has launched a digital sharia pawn service application to make it easier for customers to transact. However, until now, the lack of understanding of Andi Tonro's Sharia Pawnshop customers regarding the fees that must be paid at Sharia Pawnshops, especially Mu'nah (maintenance fees) makes customers hesitate to use the application. The purpose of this study is to analyze the application of Mu'nah (maintenance costs) in the sharia pawnshop unit andi tonro and the application of mu'nah (maintenance costs) in the Islamic pawnshop Andi Tonro unit in an Islamic perspective. The type of research used in this research is a case study with a descriptive qualitative approach. The results showed that Mu'nah (maintenance costs) in the operation of Andi Tonro's Sharia Pawnshop Unit was applied to the maintenance of each pawned item. The legal basis for implementing Mu'nah is based on MUI Fatwa 92/DSN-MUI/IV/2014 and has been approved by the OJK (Financial Services Authority). The application of Mu'nah (maintenance fees) in the operation of Andi Tonro's Sharia Pawnshop Unit continues to apply even though there are administrative costs and insurance costs. This is done to ensure that the condition of the pawned goods remains the same when it was first pawned. The application of Mu'nah (maintenance costs) at Andi Tonro's Sharia Pawnshop Unit is in accordance with Islamic teachings because in the MUI Fatwa 92/DSN-MUI/IV/2014 point six part 3 In the event that rahn (dain/marhun bih) occurs because of borrowing money (akad qardh), then Murtahin's income only comes from Mu'nah (maintenance/guarding services) for marhun whose amount must be determined at the time of the contract as ujrah in the ijarah contract. Keywords: Mu’nah;Sharia Pawnshop;Pawnshop sharia digital service.